KOMPERATIF FAKTOR WORK LIFE BALANCE (STUDI PADA MAHASISWA BEKERJA DAN TIDAK BEKERJA DI KOTA BANDUNG) - Yayan Firmansyah (Jurnal Manajemen Bisnis Performa, 2016)
The purpose of this study was to compere factors work-life balance on student work and not at some college in Bandung. The topic of work-life balance is becoming increasingly important, especially in developing countries, including one of which is Indonesia. This research was carried out by conducting a survey of students at several universities in Bandung. Analysis factors was performed using SPSS 22. This research obtains empirical findings that Family Work confict (FWC) is forming the greatest the work life balance both student work and not, as well as the work that is equal to 0.883, and 0.914. Shaping the majority is on the student group is not working "Work Family Conflict" (WFC) became the second factor shaping work life balance that is equal to 0.881.